Metagenomic and metabolomic profiling reveals the correlation between the microbiota and flavor compounds and nutrients in fermented sausages. (1st May 2022) - Yang, Peng; Zhong, Guixia; Yang, Juanchun; Zhao, Linyu; Sun, Ding; Tian, Yaqin; Li, Ruren; Rong, Liangyan
Graphical abstract: Highlights: Diverse Staphylococci are beneficial to the flavor of fermented sausages. THM-17 and SBM-52 are beneficial to the production amino acids and fatty acids. P. pentosaceus and S. xylosus are associated with l -anserine, and l -carnosine levels. P. acidilactici and S. carnosus are associated with indolelactic acid levels. Abstract: Understanding the interrelationships between the differentially abundant microorganisms and metabolites of traditional "Fuet" fermented sausages (FSs) and inoculated fermented sausages (IFSs) can help us identify key species that are missing from commercial starter cultures to reproduce the flavor compounds and nutrients of traditional Fuet FSs. IFSs, inoculated with P. pentosaceus, P. acidilactici, S. xylosus, S. carnosus (SBM-52) or P. pentosaceus, and S. xylosus (THM-17), were deficient in reproducing the volatilome profile (in particular esters, methyl aldehydes, and methyl ketones) of traditional Fuet FSs because of the lack of diverse Staphylococci ( S. carnosus, S. xylosus, S. equorum, and S. saprophyticus ). Moreover, the combination of Pediococcus and Staphylococcus were positively associated with amino acid, fatty acid, l -anserine, and l -carnosine levels. Pyridoxal and indolelactic acid levels were significantly increased in IFSs with the addition of P. acidilactici and S. carnosus, which were positively associated with vitamin B6 and tryptophan metabolic pathways.